The Effect of Auditor Opinion, Solvency, and Auditor Switching on Audit Delay with Company Size as a Moderating Variable in Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2019 - 2022 - Ikhsan M., Muhammad; Rahayu, Sri; Tiswiyanti, Wiwik (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to examine the impact of audit opinion, solvency, and auditor turnover on audit delay, accounting for the moderating variable of firm size. This study employs a quantitative research approach and utilizes secondary data acquired from the website www.idx.co.id. The populations under investigation in this study include of energy sector businesses that are publicly listed on the Indonesia Stock Exchange during the period of 2019-2022. The sampling method employed is that of purposive sampling. The sample acquired consisted of 49 firms. Indications from this study suggest that solvency positively influences audit delay. Furthermore, the impact of audit opinion and auditor turnover on audit delay is not statistically significant. The impact of audit opinion on audit delay cannot be moderated by the size of the company. The impact of fiscal solvency and auditor switching on audit time might be moderated by the size of the company.